Literary Cycling and Its Importance in the Accounts of Joseph and Elizabeth Robins Pennell - Orkun Kocabıyık (Ideas: Journal of English Literary Studies)
Elizabeth Robins Pennell and Joseph Pennell were an important couple whose Our Sentimental Journey through France and Italy (1893) and A Canterbury Pilgrimage (1887) are both about their cycling experience. While the former text is a dedication to Laurence Sterne, the latter one can be considered as the glorification of Geoffrey Chaucer, as one can clearly notice from its title. Although the bicycle was a relatively new technological development among the nineteenth-century transportation innovations, cycling and the bicycle were adopted by the society swiftly and took place as an aesthetic activity. With this aesthetic feature, in fact, this modern machine was accepted as the ideal vehicle for nostalgic travel. In this respect, Our Sentimental Journey and A Canterbury Pilgrimage can both also be read as the texts that give way to this recent invention to be perceived as a liberating vehicle; for it gave the first taste of freedom not only to working-class and middle-class people, but also to young British women such as Elizabeth Pennell herself. Considering this reciprocal relation of the two fin de siècle trends of literary travel and cycle travel, including the above-mentioned texts of the Pennells, this paper argues that cycling both enhanced and complicated the experience of literary travel for the Pennells throughout their different itineraries.